Guiding EFL learners in the use of web resources - Shiao, Chuan Kung (Penerbit UKM, 2005)
This paper describes a method of using World Wide Web resources as authentic materials in an EFL reading class. Forty-eight students enrolled in a reading class were guided in the use of websites for language learning through completing and creating scavenger hunt-type of assignments using websites that were not specifically designed for language learning. Data were collected through questionnaires, interviews and evaluation of students’ work. They revealed that despite the amount of time needed to complete the assignments, the students’ attitude towards using websites to complete English assignments was generally positive. They also became more web literate during the process of completing the assignments, especially when they collaborated to create a reading assignment using sites of their own selection.